Taurine Alleviates Intestinal Injury by Mediating Tight Junction Barriers in Diquat-Challenged Piglet Models - Wen, Chaoyue; Guo, Qiuping; Wang, Wenlong; Duan, Yehui; Zhang, Lingyu; Li, Jianzhong; He, Shanping; Chen, Wen; Li, Fengna (Frontiers in Physiology, 2020)
Background: Intestinal barrier contributes an important role in maintaining intestinal homeostasis. Oxidative stress can cause critically damages in intestinal integrity of animals. Objectives: This study was conducted to investigate the alleviated effect of taurine against small intestine (duodenum, jejunum, ileum) injury induced by oxidative stress. Methods: piglets were administered diquat and supplemented with taurine contained diet. Results: Our study revealed that oxidative stress triggered immune response, caused a serious damage of small intestinal morphology and tight junction function in diquat-induced weaned piglets. Taurine supplementation attenuated oxidative stress mainly by strengthening serum immune response, improving the villus height and the ratio of villus height/crypt depth (V/C), and decreasing the crypt depth in small intestine, and elevating the protein expression of Occlaudin and ZO-1or recovering the protein expression of Claudin-1. Conclusions: Taurine exerts protective effects by regulating immune response and restoring the intestinal tight junction barrier whenever piglets suffer from oxidative stress.